2017
DOI: 10.1016/j.gore.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade endometrial stromal sarcoma with extensive sex cord differentiation, heterologous elements, and complex atypical hyperplasia: Case report and review of literature

Abstract: HighlightsEndometrial stromal sarcoma (ESS) may have sex cord differentiation, usually focal.Diagnosis of ESS is difficult when variant morphology predominates.Prognosis differs between ESS and UTROSCT; therefore, distinction is critical.Extensive tumor sampling is mandatory to identify neoplastic endometrial stroma.Sex cord differentiation may be associated with endometrial hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Immunohistochemically, the sex cord elements in LGESS show positive staining of endometrial stromal, smooth muscle markers. Sex cord markers including inhibin, CD99, calretinin and CD56 could also be positive [19,20]. PHF1 rearrangement has been found to be predominant in the sex cord variant of…”
Section: Discussionmentioning
confidence: 98%
“…Immunohistochemically, the sex cord elements in LGESS show positive staining of endometrial stromal, smooth muscle markers. Sex cord markers including inhibin, CD99, calretinin and CD56 could also be positive [19,20]. PHF1 rearrangement has been found to be predominant in the sex cord variant of…”
Section: Discussionmentioning
confidence: 98%
“…Although some tumor cells were morphologically characterized as having cord-like differentiation in trabecular, cord, nested, or small tubular structural arrangements, no Leydig cell or Sertoli cell-like tubular sex cord-like structures were observed. Studying cases with LG-ESS-associated sex cord-like differentiation revealed that the available literature included mainly case reports, with no systematic research[3-7]. Regarding how to assess the sex cord-like differentiation in LG-ESS, we believe that in addition to the presence of the sex cord-like differentiated structures, including the trabecular, cord, or small tubular structures in the LG-ESS background, immunohistochemical assays are conducive to making assessments.…”
Section: Discussionmentioning
confidence: 99%
“…ESN and LGESS could also show sex cord-like features [3840]. According to Clement and Scully, this variant usually comprises sex cord-like elements below 50% [1], however, LGESS with a sex cord-like contribution more than 50% has also been reported [41, 42]. The tumor cells in the sex cord-like elements are small and uniform and have round or oval nuclei with inconspicuous nucleoli and scanty cytoplasm (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, nuclear atypia and mitotic activity are not prominent [41, 43]. Moreover, large foam-like or Sertoli-like cells with abundant cytoplasm have also been reported [1, 42, 43]. Immunohistochemically, the sex cord elements show positive staining of epithelial, endometrial stromal, smooth muscle markers and hormone receptors, while epithelial membrane antigen (EMA) is always negative.…”
Section: Introductionmentioning
confidence: 99%